The Effect of vermicompost and NPK fertilizer on tomato (Solanum lycopersicum) growth - Ahmad Raksun; Mohammad Liwa Ilhamdi; I wayan Merta; I Gde Mertha (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
Tomato is a plant of solanaceae family, has short stems, and grows well in tropical climates. Tomatoes have vegetative and generative growth phases. The availability of nutrients largely determines the vegetative growth phase. The purpose of the study is to determine: (1) the effect of vermicompost on tomato growth, (2) the effect of NPK fertilizer treatment on tomato growth, (3) the interaction effect of vermicompost and NPK fertilizer on tomato growth. The research was conducted using experimental methods. The research was carried out from April to July 2021. The research design was a 4 x 5 complete random factorial design with three repetitions. NPK fertilizer consisted of 4 levels of treatment doses, while vermicompost consisted of 5 levels of treatment doses. The research finding shows that the application of NPK fertilizer of 0.8 grams per plant significantly affected stem diameter, the number of compound leaves, leaf length, and stem height of tomatoes. Treatment of vermicompost of 1.8 kg of vermicompost resulted in the best stem diameter, number of compound leaves, leaf length, and stem height. The combination of vermicompost and NPK fertilizer had no significant effect on stem diameter, the number of compound leaves, leaf length, and stem height of tomatoes.